2017
DOI: 10.1186/s40168-017-0266-6
|View full text |Cite
|
Sign up to set email alerts
|

Compositionally and functionally distinct sinus microbiota in chronic rhinosinusitis patients have immunological and clinically divergent consequences

Abstract: BackgroundChronic rhinosinusitis (CRS) is a heterogeneous disease characterized by persistent sinonasal inflammation and sinus microbiome dysbiosis. The basis of this heterogeneity is poorly understood. We sought to address the hypothesis that a limited number of compositionally distinct pathogenic bacterial microbiota exist in CRS patients and invoke discrete immune responses and clinical phenotypes in CRS patients.ResultsSinus brushings from patients with CRS (n = 59) and healthy individuals (n = 10) collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
169
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(181 citation statements)
references
References 72 publications
10
169
0
2
Order By: Relevance
“…Once considered sterile, we now know that healthy sinuses contain robust and diverse microbial communities . Within the sinuses, a similar mucosal bacterial burden is present regardless of the presence or severity of sinus disease, suggesting a confluent bacterial community may saturate mucosal surfaces in both diseased and healthy sinuses . Although mucosal bacteria are similar in number across disease states, community composition varies greatly …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once considered sterile, we now know that healthy sinuses contain robust and diverse microbial communities . Within the sinuses, a similar mucosal bacterial burden is present regardless of the presence or severity of sinus disease, suggesting a confluent bacterial community may saturate mucosal surfaces in both diseased and healthy sinuses . Although mucosal bacteria are similar in number across disease states, community composition varies greatly …”
Section: Discussionmentioning
confidence: 99%
“…Barcoded primers 515F/806R were used to amplify the V4 region of the 16S rRNA gene as previously described . Amplicons were gel purified using a QIAGEN Gel Extraction kit per manufacturer protocol (QIAGEN).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was demonstrated in a study of lean and obese individuals who were better differentiated by their gut metagenome as opposed to their microbiota profile . Finally, recent biomarker sequencing studies of large patient cohorts have demonstrated that several distinct microbiota conformations are evident in patients with a given clinical indication and are related to differences in immunologic profiles and clinical features of disease . This implies that within a given diseased patient population several pathogenic microbiomes may exist; however, such possibilities remain unexplored in the field of NAFLD microbiome research.…”
Section: The Gut Microbiome In Nafldmentioning
confidence: 99%
“…The sinonasal cavity has resident microbial flora that maintains environmental homeostasis. Data of the microbiome in healthy versus diseased sinus mucosa have yielded highly variable results, but studies do suggest a dysbiosis in patients with CRS as shown by reduced microbial diversity (richness and evenness) . Of them, Staphylococcus aureus (S aureus) , a strong inducers of NETs, was found to be significantly increased in CRSwNP .…”
Section: Discussionmentioning
confidence: 99%